The Early Bird Catches the Worm! Setting a Deadline for Online Panel Recruitment Incentives. (April 2023) - Friedel, Sabine; Felderer, Barbara; Krieger, Ulrich; Cornesse, Carina; Blom, Annelies G.
The literature on the effects of incentives in survey research is vast and covers a diversity of survey modes. The mode of probability-based online panels, however, is still young and so is research into how to best recruit sample units into the panel. This paper sheds light on the effectiveness of a specific type of incentive in this context: a monetary incentive that is paid conditionally upon panel registration within two weeks of receiving the initial postal mail invitation. We tested early bird cash incentives in a large-scale recruitment experiment for the German Internet Panel (GIP) in 2018. We find that panel response rates are significantly higher when offering early bird cash incentives and that fieldwork progresses considerably faster, leading to fewer reminders and greater cost-effectiveness. Furthermore, sample representativeness is similarly high with or without early bird incentives.